Teori Desentralisasi Dan Pemerintahan Lokal Pada Masa Parlementer (1950-1959) - Sendika, May; Naldi, Hendra; Frinaldi, Aldri; Magriasti, Lince (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
The Parliamentary Democracy Period (1950-1959) was a crucial period in laying the foundations for decentralization and local government in post-independence Indonesia. This article aims to analyze the theory and practice of decentralization and local government in that era using qualitative research methods through the approach of literature study and historical analysis. This research focuses on tracing the applicable main law, namely Law No. 1 of 1957 concerning the Principles of Regional Government, and analyzing it through a theoretical lens put forward by experts such as Joko Kirmanto, Sadu Wasistiono, and Utang Rasidin. The findings of the study show that although theoretically Law No. 1/1957 represents significant progress by adopting a model of real and widespread autonomy, in practice its implementation is faced with complex challenges. The dominant factors are national political instability, diversity of interpretations at the local level, and the still strong centralist of the colonial legacy bureaucracy. This article concludes that the Parliamentary period succeeded in creating a democratic decentralization blueprint, but failed to realize it effectively, providing valuable lessons for the development of regional autonomy in later eras.